Metrology for pH Measurements in Brackish Waters—Part 1: Extending Electrochemical pHT Measurements of TRIS Buffers to Salinities 5–20 - Müller, Jens D.; Bastkowski, Frank; Sander, Beatrice; Seitz, Steffen; Turner, David R.; Dickson, Andrew G.; Rehder, Gregor (Frontiers in Marine Science, 2018)
Harned cell pHT measurements were performed on 2-amino-2-hydroxymethyl-1,3-propanediol (TRIS) buffered artificial seawater solutions in the salinity range 5 20, at three equimolal buffer concentrations (0.01, 0.025, 0.04 mol·kg H2O 1), and in the temperature range 278.15 – 318.15 K. Measurement uncertainties were assigned to the pHT values of the buffer solutions and ranged from 0.002 to 0.004 over the investigated salinity and temperature ranges. The pHT values were combined with previous results from literature covering salinities from 20 to 40. A model function expressing pHT as a function of salinity, temperature and TRIS/TRIS·H+ molality was fitted to the combined data set. The results can be used to reliably calibrate pH instruments traceable to primary standards and over the salinity range 5 to 40, in particular, covering the low salinity range of brackish water for the first time. At salinities 5-20 and 35, the measured dependence of pHT on the TRIS/TRIS·H+ molality enables to extrapolate quantities calibrated against the pHT values, e.g. the dissociation constants of pH indicator dyes, to be extrapolated to zero TRIS molality. Extrapolated quantities then refer to pure synthetic seawater conditions and define a true hydrogen ion concentration scale in seawater media.